2020
DOI: 10.1097/prs.0000000000006837
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Quality-of-Life Outcomes after Facial Feminization Surgery: An International Multicenter Study

Abstract: Background: No data exist on the prospective outcomes of facial feminization surgery. This study set out to determine the effects of facial feminization surgery on quality-of-life outcomes for gender-diverse patients. Methods: A prospective, international, multicenter, cohort study with adult gender-diverse patients with gender dysphoria was undertaken. Facial feminization outcome score was calculated preoperatively and postoperatively (1-week to 1-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 44 publications
4
88
0
11
Order By: Relevance
“…The prioritization of facial feminization surgery (FFS) over other forms of gender reassign-ment surgery among transgender individuals reflects the important role it plays in gender dysphoria [1,2]. Studies such as those by Ainsworth and Spiegel [3], and more recently by Morrison et al [4], have revealed its positive effects on mental health-related quality of life. Objective studies of public perception have also demonstrated significant differences in gender appearance from FFS beyond what hormone or non-surgical therapy can Evaluation and treatment of facial feminization surgery: part I. forehead, orbits, eyebrows, eyes, and nose provide [5].…”
Section: Introductionmentioning
confidence: 99%
“…The prioritization of facial feminization surgery (FFS) over other forms of gender reassign-ment surgery among transgender individuals reflects the important role it plays in gender dysphoria [1,2]. Studies such as those by Ainsworth and Spiegel [3], and more recently by Morrison et al [4], have revealed its positive effects on mental health-related quality of life. Objective studies of public perception have also demonstrated significant differences in gender appearance from FFS beyond what hormone or non-surgical therapy can Evaluation and treatment of facial feminization surgery: part I. forehead, orbits, eyebrows, eyes, and nose provide [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the first study to assess prospective outcomes of FGCS, Morrison et al evaluated facial feminization outcome scores, photogrammetric cephalometrics, selfperceived masculinity and femininity, externally rated gender appearance, and general aesthetics of 66 consecutive patients in an international, multicentered trial (12). All outcomes were favorable in the six months follow-up period with median facial feminization outcome scores increasing from 47.2 to 80.6 (scale out of 100, higher scores denote more feminine appearance.…”
Section: Discussionmentioning
confidence: 99%
“…For many transgender patients the face is a source of significant dysphoria and addressing this can increase the patient's quality of life and unify his/her physical Review Article on Transgender Surgery features and self-image (4). Although there has only been one international, prospective, international, multicenter, cohort study on FFS demonstrating improved quality of life, the daily impact of the results of these procedures are unequivocally positive (5)(6)(7)(8)(9)(10)(11)(12).…”
Section: History Of Facial Gender Confirmation Surgery (Fgcs)mentioning
confidence: 99%
“…17 Studies have shown that insurance coverage of transgender care is cost-effective, with a low budget impact at the societal level, improved quality-adjusted life years, and decreased incidence of HIV and drug abuse. 70 Similar studies have shown that quality of life scores are improved after facial feminization specifically, 71 but longer term studies are also needed to define the outcomes of facial masculinization procedures. These outcomes are particularly valuable in appealing negative coverage determinations, as many insurance company policies dictate that medical necessity is dependent on a patient's manifestation of gender dysphoria.…”
Section: Advocating For Policy Changementioning
confidence: 99%